Der Midrasch zur Eschatologie aus der Qumrangemeinde (4QMidrEschata̳.̳b̳) : materielle Rekonstruktion, Textbestand, Gattung und traditionsgeschichtliche Einordnung des durch 4Q174 ("Florilegium") und 4Q177 ("Catena A") repräsentierten Werkes aus den Qumranfunden - Steudel, Annette. (Studies on the Texts of the Desert of Judah, 1994)
This volume deals with one of the oldest midrashim, the Eschatological Midrash from Qumran Cave 4. 4QMidrEschat, previously unknown, is preserved in at least two copies (4QFlorilegium, 4QCatena A) found at Qumran. A reconstruction of 4QFlorilegium and 4QCatena A is given in the first part of the book. The second part is a comparative analysis which shows that both manuscripts are copies of the same former work, 4QMidrEschat. The third part deals with the other exegetical Qumran texts, a definition of 4QMidrEschat's genre, its position among the Qumran literature, and its dating. 4QMidrEschat provides valuable information on Bible interpretation and eschatology among the Essenes in the first century BCE. 4QMidrEschat is of special significance because, according to recent studies, the Essenes are no longer to be regarded as a \'sect\', but as one of the most important Jewish groups of that time.